Variable speed pumping : a guide to successful applications (Elsevier, 2004)
Prepared by industry experts from the pump, motor and drive industries under the auspices of Europump and the Hydraulic Institute, this reference book provides a comprehensive guide to variable speed pumping. It includes technical descriptions of pumping systems and their components, and guides the reader through the evaluation of different speed control options. Case studies help illustrate the life cycle cost savings and process improvements that appropriate variable speed pumping can deliver.